Removal of mercury (II) ion from industrial wastewater using palm oil fuel ash - Imla Syafiqah, Mohd Salleh (2018)
Activated palm oil fuel ashes (POFA) were used as the adsorbents for the removal of mercury (II) ion from industrial wastewater. From the preliminary experimental results, it shows that the POFA had good adsorption capability for mercury (II) ion. The adsorption process of mercury (II) ion using POFA not only contributes to the mercury adsorption from industrial wastewater but also removes the environmental pollution caused by accumulation and abundance of waste in nature. Therefore, POFA was introduced as a raw material in this study to maximize the utilization of oil palm waste. POFA was activated using chemical activation and sulphuric acid used as a solvent before proceeding with mercury (II) ion adsorption process. Scanning electron microscopy (SEM), fourier transform infrared spectrometry (FTIR), thermal gravimetric analysis (TGA), and Brunauer-Emmett-Teller (BET) surface area analysis had been applied to observe the effect of the POFA structure before and after activation. The screening study was analyzed using fractional factorial design (FFD). In factorial analysis study, the best mercury (II) ion removal condition removed 98.03 ± 0.06 % when performed at 100 rpm of agitation speed, pH 2, 5 mg/L of initial mercury (II) ion concentration, 0.25 g of adsorbent dosages and 4 h of contact time. From this screening study, two factors which are contact time and agitation speed were selected for further analysis in optimization part. The optimization of mercury (II) ion removal efficiency was done by using central composite design (CCD) in response surface methodology (RSM). In central composite design (CCD), the optimum condition for mercury (II) ion removal was obtained at 150 rpm for 5 h which removed 98.93 ± 0.02 % of mercury (II) ion. The equilibrium data at various concentrations were analysed by Langmuir and Freundlich isotherms models. From this present study, the values of correlation coefficient (R2) obtained from the Freundlich isotherm was 0.9899. A kinetic study was carried out with pseudo first order and pseudo second order reaction equations. It was found that the mercury (II) ion uptake process followed the pseudo second order rate expression. Thermodynamic parameters of the Gibbs free energy (Δ